APPLICATION OF THE ROLE PLAYING METHOD TO IMPROVE SPEAKING SKILLS IN CLASS V STUDENTS OF UPT SPF SD NEGERI BADDOKA KECAMATAN BIRINGKANAYA KOTA MAKASSAR - Assagaf, S. Risma Purnamayanti (Publikasi dan UKI Press UKI Toraja., 2023)
The problem in this research is the low learning outcomes of students in learning speaking skills. The formulation of the problem in this research is how to apply the Role-Playing method to improve speaking skills in class V students at UPT SPF SD Negeri Baddoka, Kecamatan Biringkanaya, Kota Makassar. Based on the problem formulation, the researcher carried out a follow-up with classroom action research consisting of 4 patterns, including: planning, implementation, observation, and reflection using the Role-Playing method. The type of research used is classroom action research (PTK) and the approach used in this research is a qualitative approach. The focus of this research is the application of the Role-Playing method and students' speaking skills. The subjects of this research were 1 teacher and 34 students. Data collection is carried out through observation, tests and documentation. In this research, learning refers to learning steps using the Role-Playing method, namely starting from the learning preparation stage, the learning implementation stage, and the final learning stage. The data analysis technique used in this research is descriptive qualitative. Data from observations of teacher teaching activities and student learning activities experienced an increase, which in cycle I was in the sufficient category and in cycle II it increased to the good category. The research results of students' speaking skills in cycle I were in the sufficient category and in cycle II they increased to good category. Thus, it can be concluded that the application of the Role Playing method can improve speaking skills in class V students at UPT SPF SD Negeri Baddoka, Kecamatan Biringkanaya, Kota Makassar